Can rights-based conditional cash transfers improve children’s nutrition at scale? Evidence from India’s maternity benefit program - Ray, Soumyajit; Chakrabarti, Suman; Pal, Sumantra; Nguyen, Phuong Hong; Scott, Samuel P.; Menon, Purnima (MedRxiv, 2025)
This study evaluates the impact of India’s Pradhan Mantri Matru Vandana Yojana (PMMVY), a large-scale conditional cash transfer (CCT) program targeting women during their first birth, on child nutrition. Using National Family Health Survey (NFHS) data from 2005 to 2021, we assess changes in growth for 296,782 children under five years old before and after PMMVY implementation. To address potential biases, we employ a quasi-experimental approach with a Triple Difference analysis, comparing first- to second-born children of CCT and non-CCT mothers. We find that potential exposure to PMMVY is associated with improvements in weight-for-age and height-for-age z-scores. These effects likely operate through increased pregnancy registration, antenatal care, and immunizations. PMMVY is cost-effective, with a short-run benefit-cost ratio of 1.35. This study underscores the importance of CCT programs targeting mothers in enhancing child nutrition in low- and middle-income countries.